Smart Analysis (Speed Movement Acceleration Reaction Time) Based on Windows Applications for Increasing the Effectiveness of Volleyball Athletes' Spikes - Firman Adityatama; Dicky Reva Apriana Sanga Dwi; Oman Hadiana; Sartono Sartono (JUARA : Jurnal Olahraga, 2022)
This study aims to develop motion analysis using kinovea software. The research method used is research and development of the ADDIE model, which consists of 5 stages, namely (1) analysis, (2) design, (3) development, (4) implementation, (5) and evaluation. The sample used was 30 students of the STKIP Muhammadiyah Kuningan volleyball student activity unit (UKM). The results showed that this training model was valid, practical, and effective. Validity: expert judgment for the material score is 3.95, and expert judgment media produces an average score of 3.95, both in the valid category. Practical: the average response to the small-scale questionnaire was 3.71 (good), the average response to the small group trial questionnaire was 3.84 (good), and the average response to the field trial questionnaire was 3.51 (good). Effectiveness: n-gain test value 0.56 (medium). It can be concluded that the application of the Kinovea software to analyze the basic spike technique in volleyball has a significant contribution.